The Moderating Role of Knowledge in The Effect of News Access on Students’ Political Participation in Makassar - Raidah Intizar Yusuf; Nahdiana Nahdiana; Anil Hukma; Andriansyah Andriansyah; Pramudita Budi Rahayu (Universitas of Muhammadiyah Makassar, 2023)
The 2019 student protests prompt the question of whether access to political news affects political participation, with political knowledge serving as a moderating factor. It is suggested that access to political news, as a source of political education for students, may have an impact on political participation. When students who are well-informed have access to political news, they are likely to engage in higher levels of political participation, with political knowledge acting as a moderating variable in this relationship. This study aims to investigate the relationship between access to political news, political knowledge, and political participation (both online and offline) among students. This is the first time that political knowledge is being analyzed as a factor that may amplify the effect of access to political news on participation. This study is a quantitative survey research that was administered to 465 students in Makassar. Of the participants, 64.7% were female (N = 301) and 35.3% were male (N = 164) with an average age of 20.54 (SD = 1.80). The data was analyzed using multiple regression analysis by entering predictor variables and interaction variables, where the predictor variable is multiplied to determine the moderating effect of each predictor on the outcome variable. It found that access to political news is a significant predictor of both types of political participation, and that political knowledge moderates this relationship. This study conluded that political knowledge can act as a counter to potentially misleading information and news, furthermore with sufficient knowledge accumulation will result in real participation, both online and offline.